Smart Tourism Technology as a Driver of Vivid Memory and Behavioral Intention: Evidence from Domestic Tourists in Indonesia - Trixie Nova Bella Tandijaya; Regina Jokom; Hatane Semuel; Sienny Thio (Jurnal Bisnis dan Manajemen, 2026)
While the integration of Smart Tourism Technology (STT) is recognized as critical for destination competitiveness, empirical understanding of how individual digital touchpoints translate into lasting cognitive imprints and behavioral outcomes remains fragmented. This study examines how STT attributes shape Vivid Memory and Behavioral Intention among domestic tourists in Indonesia. Employing a quantitative approach, data were collected from 389 tourists who had visited four priority destinations (Bali, Yogyakarta, Surabaya, and Manado) and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that the Informativeness and Personalization dimensions enhanced Vivid Memory, whereas Accessibility and Interactivity do not show significant effects. Furthermore, Vivid Memory is proven to have a dominant influence on Behavioral Intention. These results indicate that smart technology does not automatically drive post-visit intentions; rather, its effect is psychologically mediated by the vividness of the memories it helps create. Theoretically, this study challenges monolithic smart tourism paradigms by demonstrating an asymmetric, dual-factor mechanism where baseline operational tech functions merely as a hygiene prerequisite, whereas content-driven attributes act as true motivational memory triggers. Practically, it guides destination managers to shift resource allocation from generic digital infrastructure toward AI-enabled personalization and digital narrative storytelling to maximize tourist memory retention.